Direct Method Translation of Descriptive Text from English into Indonesian - Sinurat, Bloner; E. Silalahi, Dumaris; Saputra, Nanda (Journal of Social Science and Humanities Research, 2022)
The objective of the research is to find out the extent of direct translation at the eighth grade students of SMP Negeri 6 Pematangsiantar in the translation descriptive text from English into Indonesianin academic year 2019/2020.The problem research is about what extent of direct translation method are used at grade eight students of SMP N 6 Pematangsiantar in the translation descriptive text from English into Indonesian?. To solve the problems, the research used theories Vinay and Darbelnet in Venuti (2000:84-93) divided translation procedures into two namely Direct or Literal Translation which cover three procedures (borrowing, calque, and Literal translation). The research uses qualitative descriptive method. The data was taken from grade VIII-2 SMPN 6 Pematangsiantar with the total number of students are twenty students. The researcher takes 20 students to analyze the students’ translating. Then, the researcher analyzes the data, describe and classify their translation. The research finding of the thesis showthat the students’ translation borrowing translatiom 22,2%, calque translation 19,05%, literal translation 58,73% but some students did not get transferring the meaning of text so the students did not complete to translate the text. The researcher concludes that some students always found many difficulties in translation because they do not understand meaning word, the usage of structure in sentences and confused within the text.